2020
DOI: 10.18549/pharmpract.2020.3.1928
|View full text |Cite
|
Sign up to set email alerts
|

The role of the community pharmacist in veterinary patient care: a cross-sectional study of pharmacist and veterinarian viewpoints

Abstract: Background: The role of the community pharmacist is rapidly expanding to encompass the care of veterinary patients in the United States of America This change makes it imperative for pharmacists and veterinarians who practice in community settings to establish mutual agreement on the roles of pharmacists in the care of these patients. Objective: To examine community-based pharmacist and veterinarian viewpoints on interprofessional collaboration and the role of the community pharmacist in veterinary patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…There are also gaps in the awareness of AMR and the links between ABU and AMR in our study, similar to other studies [ 67 , 71 ]. This suggests a need for pharmacy professionals to work closely with veterinary professionals and related stakeholders in developing and instigating strategies to curb unnecessary ABU to prevent the adverse consequences of AMR [ 99 ]. This can build on our findings that most of the participants in our study knew about the uses and withdrawal periods of antibiotics, similar to studies in Bangladesh and Bhutan [ 71 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also gaps in the awareness of AMR and the links between ABU and AMR in our study, similar to other studies [ 67 , 71 ]. This suggests a need for pharmacy professionals to work closely with veterinary professionals and related stakeholders in developing and instigating strategies to curb unnecessary ABU to prevent the adverse consequences of AMR [ 99 ]. This can build on our findings that most of the participants in our study knew about the uses and withdrawal periods of antibiotics, similar to studies in Bangladesh and Bhutan [ 71 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another field of interest concerns veterinary medicine, as community pharmacists are increasingly being involved in dispensing animals’ medications [ 91 , 92 ]. The extensive use of antibiotics in animal husbandry is considered an important contributor to microbial resistance, as antibiotics are not only used in treatment of developed infection but also as a growth promotor factor or prophylactic, often administered to an entire stock of animals [ 93 , 94 ].…”
Section: Antimicrobial Stewardship In Community Pharmacymentioning
confidence: 99%
“…Another concerning practice was discovered by a study in India where the veterinary antimicrobial medications for working animals were dispensed intentionally in wrong dosages and in higher quantities for financial gain [ 105 ]. Another obstacle in ensuring the proper use of antimicrobial drugs was the pharmacists’ perceived lack of knowledge about veterinary pharmacology, further potentiated by the lack of developed guidelines about antibiotics use in animals [ 91 , 92 ].…”
Section: Antimicrobial Stewardship In Community Pharmacymentioning
confidence: 99%
“…A 2020 survey revealed that only 22% of responding veterinarians felt confident in the ability of the pharmacist filling and counseling on veterinary medications. 8 However, there is a paucity of data available to describe medication and prescription errors made by veterinarians. This is especially important after a recent conference presentation that reported only 22.2% of veterinary students are being taught prescription writing and 35.7% of veterinarians do not consult with a pharmacist when training veterinary students to write prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…This collaborative focus is echoed in a study that found 84% of veterinarians and 92% of pharmacists are interested in collaborating with their local counterparts. 8 Assessment of prescription errors and the resulting responsible party is vitaldnot in laying blame but in understanding how and why errors occurred so that future errors can be prevented. Identifying the prevalence of veterinary prescription errors and establishing what the most common errors are and at what point in the prescribing process they occur will enable the development of effective continuing pharmacy education opportunities and advancement of interprofessional collaboration between pharmacists and veterinarians.…”
Section: Introductionmentioning
confidence: 99%